Psychological Distress and Use of Psychotropic Drugs Among University Students—the SHoT Study, Norway - Bojanić, Ivana; Sund, Erik R.; Bjerkeset, Ottar; Sivertsen, Børge; Sletvold, Hege (Frontiers in Psychiatry, 2021)
Background: Students pursuing higher education are struggling with psychological distress, which in turn may negatively affect their academic self-efficacy and study progress. Although psychotropic drug use is widespread and increasing, patterns of psychotropic drug use among students are not well known. Aim: To describe prevalence and gender differences in psychotropic drug use among Norwegian students in higher education, and to examine associations with level of psychological distress. Methods: The study is based on data from the Norwegian Student’s Health and Wellbeing Study (SHoT), 2018, a national survey including all fulltime students aged 18-35 years in higher education. Our sample included 49,836 students, 69% females. Use of psychotropic drugs and psychological distress (The Hopkins Symptoms Checklist [HSCL-25]) were self-reported. Generalized linear models were used to assess associations between psychological distress and psychotropic drug use. Results: Psychotropic drug use was more frequent among female than male students: 4% vs 2% daily antidepressants usage; 5% vs 3% last month use of anxiolytics/tranquillisers; and 8% vs 5% last month use of hypnotics. In contrast, male students reported use of performance enhancing drugs more often than females (5% vs 7%). Adjusted associations between high level of psychological distress (HSCL-25 ≥ 2.0) and use of psychotropics, showed an about two-fold increased relative risk, largely consequent across drug classes and genders. Conclusion: Prevalence and gender patterns of intake of the most common psychotropic drug classes among Norwegian students are comparable to previous studies. Unexpectedly, among students with moderate to severe psychological distress, the patterns of psychotropic drug use were more or less identical between genders.